2010
DOI: 10.1159/000320029
|View full text |Cite
|
Sign up to set email alerts
|

Three New SF-1 <i>(NR5A1) </i>Gene Mutations in Two Unrelated Families with Multiple Affected Members: Within-Family Variability in 46,XY Subjects and Low Ovarian Reserve in Fertile 46,XX Subjects

Abstract: Background: Three novel heterozygous SF-1 gene mutations affecting multiple members of two unrelated families with a history of 46,XY disorders of sex development (DSD) and 46,XX ovarian insufficiency are described. Methods: Clinical and mutational analysis of the SF-1 gene in 9 subjects of two families. Results: Family 1 had 2 affected 46,XY DSD subjects. One, born with severe perineal hypospadias, was raised as a male, and presented normal adolescence. The other, born with ambiguous genitalia, uterus, and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 75 publications
10
64
0
Order By: Relevance
“…Warman et al reported a family with six members harbouring a heterozygous NR5A1 hinge region mutation (p.Tyr183X) and displaying a wide range of different phenotypes. Three affected members had isolated hypospadias, two of whom were severe perineal and one was mild glandular (9). Another case of isolated distal hypospadias carrying a de novo heterozygous missense mutation (p.Arg313Cys) located at the end of the ligand-binding domain of the NR5A1 gene was reported by Allali et al (10) ( Table 2).…”
Section: European Journal Of Endocrinologymentioning
confidence: 89%
See 1 more Smart Citation
“…Warman et al reported a family with six members harbouring a heterozygous NR5A1 hinge region mutation (p.Tyr183X) and displaying a wide range of different phenotypes. Three affected members had isolated hypospadias, two of whom were severe perineal and one was mild glandular (9). Another case of isolated distal hypospadias carrying a de novo heterozygous missense mutation (p.Arg313Cys) located at the end of the ligand-binding domain of the NR5A1 gene was reported by Allali et al (10) ( Table 2).…”
Section: European Journal Of Endocrinologymentioning
confidence: 89%
“…So far, there is no apparent genotype-phenotype correlation in patients with NR5A1 mutations. The phenotypic spectrum has been extended, involving not only ambiguous genitalia and hypospadias due to gonadal dysgenesis (8,9,10), but also vanishing testis syndrome (11), isolated hypoplastic penis (12) and male infertility (13,14). Moreover, NR5A1 mutations were also found in 46,XX females with premature ovarian failure and primary ovarian insufficiency (15,16,17,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Partial hypogonadotropic hypogonadism, necessitating testosterone supplementation during puberty has been documented in one male patient with penoscrotal hypospadias and a L437Q mutation in the NR5A1 ligand-binding domain (8). Recently, normal pubertal progression, with low Inhibin B but normal LH and FSH concentrations has been reported in two adolescents with a milder phenotype (12). In this study, we report on spontaneous and advanced androgenization in two adolescents who were poorly virilized at birth and sexassigned female, with reassignment to male in one patient at the age of 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of patients affected by NR5A1 mutations is very diverse, ranging in 46,XY individuals from phenotypically females with complete gonadal dysgenesis with or without adrenal failure (5)(6)(7)(8)(9)(10) to males with penoscrotal hypospadias (8,11,12) or bilateral anorchia (13). In 46,XX women, NR5A1 mutations have been associated with premature ovarian failure (3).…”
Section: Introductionmentioning
confidence: 99%
“…However, a clear correlation between the location of a mutation, its in vitro functional performance, and the associated phenotype is not observed. Indeed, family members bearing the same NR5A1 mutation may present with variable phenotypes (Warman et al, 2011). …”
Section: Discussionmentioning
confidence: 99%